The Effect of Progressive Relaxation Exercises on Fatigue Levels of Patients: A Systematic Review - NAS, İbrahim; AYDIN, Esra; AKPINAR, Reva Balcı (Göbeklitepe Medical Science Journal, 2022)
Fatigue is a symptom that prevents the individual from using his functions and normal capacity, affects the whole body, impairs the quality of life, and is an important complaint especially in individuals with chronic diseases. Progressive relaxation exercises are among the complementary therapies that can be helpful in reducing fatigue. In this systematic review, articles investigating the effects of progressive relaxation exercises on patients' fatigue levels were evaluated. Twenty-six research articles with experimental/semi-experimental, randomized/non-randomized control groups, published in Turkish and English between January 2000 and December 2021, were included in the evaluation. In the articles evaluated, it was determined that the study groups mostly consisted of individuals with chronic diseases such as cancer, hemodialysis, heart, multiple sclerosis, type II diabetes, rheumatoid arthritis, fibromyalgia, chronic obstructive pulmonary disease. In all articles included in the study, it was found that progressive relaxation exercises reduce fatigue.